Sociology of Tree Marriages: Patriarchy, Purity, and Protection in Customary Law - Bhoi, Chandrasekhar (International Journal of Multidisciplinary Approach Research and Science, 2025)
This article examines the sociological significance of "tree marriages," a ritualistic practice predominantly observed in parts of South Asia, particularly India. Symbolic in nature but rooted in real social implications, these ceremonies reflect deeply entrenched patriarchal values masked as spiritual or protective customs. Often conducted in response to astrological beliefs — particularly the presence of a “manglik dosha” in a woman’s horoscope — these symbolic unions are believed to mitigate supposed cosmic threats to future human marriages. However, beneath the veneer of religious or cultural tradition lies a complex system of gender regulation, where women's lives and marital prospects are shaped by rituals that restrict autonomy while appearing to offer protection. This study explores the role of tree marriages in reinforcing gender hierarchies, controlling female agency, and maintaining cultural purity through customary law. It investigates how these practices function as social technologies that uphold caste endogamy, manage inheritance, and safeguard family honor. By synthesizing sociological theory, legal pluralism, and gender analysis, the article provides a comprehensive understanding of how tree marriages serve both symbolic and practical purposes in sustaining patriarchal order. In doing so, it challenges the normative acceptance of such practices and calls for critical re-examination of tradition-based gender roles in contemporary societies.